Chloroplast structure and DNA methylation polymorphisms in an albino mutant of wheat (Triticum aestivum)cv. Xinong 1376 - Song, Y.; Tang, H.; Ke, X.; Guo, J.; Zhang, S.; Wang, J.; Zhang, G.
DNA methylation plays an important role in regulating plant development, including organ and tissue differentiation, which may determine variations in agronomic traits. However, no reports exist for the regulation of leaf colour in wheat. The present study investigated the chloroplast structure and epigenetic mechanisms regulating leaf colour in an albino mutant of wheat (Triticum aestivum L.)cv. Xinong 1376. Structural analysis was performed by scanning and transmission electron microscopy, and epigenetic modifications were detected by methylation-sensitive amplification polymorphism (MSAP)analysis. Mesophyll cells of green leaves showed a well-ordered arrangement and they were filled with chloroplasts with intact lamellar structures and thylakoid membranes. By contrast, mesophyll cells of red and white leaves were disorganised and contained only a few plastids or chloroplasts with no lamellar structures or thylakoid membranes. Comparison of MSAP profiles revealed that white or red leaves had higher levels of cytosine methylation and showed changes in polymorphic loci compared with green leaves (4.35 percent and 4.10 percent, respectively). We sequenced 150 DNA fragments that were differentially displayed in MSAP patterns of white or red and green leaves of the Xinong 1376 albino mutant. A further BLAST search of 77 cloned sequences located them in coding regions. Most of these sequences were found to be involved in processes such as signal transduction, transcription regulation, post-transcriptional processing, DNA modification and repair, transport, biosynthesis of cellulose, photosynthesis, protein ubiquitination, stress responses, and retroposition. Expression analysis demonstrated a decrease in the transcription of two methylated genes, psaA and psbD, which are involved in the photosystem. Although the DNA methylation changes and leaf colour changes were not directly associated, these results may indicate that methylation of specific genes is an active and rapid epigenetic response to variation of leaf colour in the Xinong 1376 albino mutant, further elucidating the mechanism of variation in leaf colour.
Keywords: ALBINISM; LEAF; METHYLATION; PHOTOSYNTHESIS